2019
DOI: 10.1186/s13071-019-3386-y
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania infantum-specific IFN-γ production in stimulated blood from cats living in areas where canine leishmaniosis is endemic

Abstract: BackgroundFeline leishmaniosis caused by Leishmania infantum is considered a rare disease in endemic areas, whereas subclinical infections are common. Immune response plays a key role in driving the course of L. infantum infection in other host species; however, the feline cell-mediated immune response to L. infantum infection has not yet been investigated. The aim of this study was to determine the cell-mediated immune response specific to L. infantum by means of interferon (IFN)-γ release in whole blood assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 29 publications
1
20
0
2
Order By: Relevance
“…This variability is thought to be the result of a cell-mediated immune response from the host, which may be influenced by the genetic background. A similar pattern of humoral and cell-mediated adaptive immune response is detected in cats from endemic areas of L. infantum [6]. The most common clinical signs of feline leishmaniosis (FeL) include peripheral lymphadenomegaly, cutaneous and mucocutaneous lesions (e.g.…”
Section: Introductionmentioning
confidence: 78%
“…This variability is thought to be the result of a cell-mediated immune response from the host, which may be influenced by the genetic background. A similar pattern of humoral and cell-mediated adaptive immune response is detected in cats from endemic areas of L. infantum [6]. The most common clinical signs of feline leishmaniosis (FeL) include peripheral lymphadenomegaly, cutaneous and mucocutaneous lesions (e.g.…”
Section: Introductionmentioning
confidence: 78%
“…Recently, it has been described that cats from endemic areas are able to activate a cell-mediated adaptive immune response. 75 However, other authors have suggested that the humoral immune response is protective in FeL, 1,76 highlighting the potential differences in the immune response between these two species. In some dogs, the simultaneous presence of more than one presentation could be due to other factors, such as skin vulnerability to mechanical trauma and/or to vascular compromise, 48,77 and that might be the case in some cats.…”
Section: Discussionmentioning
confidence: 99%
“…Older studies from Southern Italy found 7% positivity in Campania [71]. Around the same time and in the following years, no FeLV-positive samples were found in Sicily in studies including stray or outdoor cats [72,73,74,75,76,77], or about 2% positivity was reported in the Sicily [78,79] and Calabria regions [72]. Regional differences in the prevalence of FeLV infection have likely existed for some time within Italy.…”
Section: Discussionmentioning
confidence: 99%